Ultrahigh-strength TiB2 / Al-Mg-Si conductor material and preparation method thereof

By adding TiB2 hard ceramic particles to Al-Mg-Si aluminum alloy and using multi-step process optimization, the problems of complex production processes and insufficient performance of the existing Al-Mg-Si aluminum alloy wires have been solved, and the high elastic modulus, strength and conductivity have been improved, which is suitable for large-scale production.

CN119663062AActive Publication Date: 2025-03-21STATE GRID LIAONING SHENYANG ELECTRIC POWER SUPPLY COMPANY +3
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411759924.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-03-21
Estimated Expiration
2044-12-03

AI Technical Summary

Technical Problem

The existing Al-Mg-Si aluminum alloy conductors have complex production processes, and the market has increasingly demanded for its sag characteristics, strength and conductivity, making it difficult to meet the demand for high-performance aluminum conductor materials.

Method used

By adding TiB2 hard ceramic particles to the Al-Mg-Si aluminum alloy, the composition and microstructure of the material are optimized by smelting, homogenizing annealing, hot extrusion deformation, solid solution treatment, artificial aging and room temperature drawing.

Benefits of technology

The high elastic modulus, strength and conductivity of the material are improved, and the better sag characteristics are obtained. The process is simple and easy to promote, and it is suitable for large-scale mass production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119663062A_ABST
    Figure CN119663062A_ABST
Patent Text Reader

Abstract

The invention discloses an ultrahigh-strength TiB2 / Al-Mg-Si conductor material and a preparation method thereof, and the conductor material comprises the following components in percentage by mass: 1.1-1.6% of Ti, 0.4-0.9% of B, 0.6-0.9% of Mg, 0.6-0.9% of Si, less than 0.2% of Fe impurity, less than 0.1% of other impurities, and the balance of Al. The preparation method of the conductor material comprises the following steps: step 1, smelting: remelting and diluting an Al-TiB2 precursor to prepare a TiB2 / Al-Mg-Si porcelain steel aluminum alloy cast ingot; step 2, homogenizing annealing; 3, hot extrusion deformation is conducted, and an extrusion rod is obtained; step 4, solution treatment; 5, artificial aging is conducted; 6, drawing at room temperature; and 7, low-temperature artificial aging is carried out, and the ultrahigh-strength TiB2 / Al-Mg-Si conductor material is obtained. The preparation method provided by the invention is tightly combined with a traditional aluminum conductor material preparation process, is easy to popularize, and can be used for large-scale batch production. The ultrahigh-strength TiB2 / Al-Mg-Si conductor material disclosed by the invention has excellent mechanical property and conductivity, the elastic modulus of the ultrahigh-strength TiB2 / Al-Mg-Si conductor material is 73.0-73.3 GPa, the tensile strength of the ultrahigh-strength TiB2 / Al-Mg-Si conductor material is 404.2-409.4 MPa, and the conductivity of the ultrahigh-strength TiB2 / Al-Mg-Si conductor material is 56.3-56.5%
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of material technology, and in particular to an ultra-high strength TiB2 / Al-Mg-Si conductor material and a preparation method thereof. Background Art

[0002] Large-capacity, long-distance, and long-span overhead transmission lines are the main carriers of long-distance power transmission, and high-performance aluminum conductor materials have become an urgent need for the construction of long-span overhead transmission lines. Overhead transmission lines not only need to have high enough conductivity to reduce line losses, but also need to have sufficient strength to withstand their own weight and withstand harsh service conditions, such as wind loads, icing, and atmospheric corrosion, which are serious threats to the safe operation of the power system.

[0003] All-aluminum alloy stranded wire generally uses Al-Mg-Si alloy as the conductor material. Al-Mg-Si alloy wire not only has good electrical conductivity and high tensile strength, but also has good corrosion resistance and welding performance, and has a series of advantages such as large capacitance, light weight, and good sag performance. The large-scale production and application of Al-Mg-Si alloy wire puts forward very high requirements on process equipment such as continuous casting and rolling, drawing, heat treatment and artificial aging. Its mechanical properties and electrical conductivity are very sensitive to work hardening, solid solution and aging, so the production process window of high-performance Al-Mg-Si aluminum alloy wire is very narrow.

[0004] In summary, developing a production process for high-performance Al-Mg-Si aluminum alloy wire is an urgent problem to be solved. Summary of the invention

[0005] In view of this, the present invention provides an ultra-high strength TiB2 / Al-Mg-Si conductor material and a preparation method thereof to obtain an ultra-high strength TiB2 / Al-Mg-Si conductor material with high elastic modulus, strength and conductivity.

[0006] The technical solution provided by the present invention is specifically, an ultra-high strength TiB2 / Al-Mg-Si conductor material, which comprises, by weight percentage:

[0007] Ti 1.1-1.6%, B 0.4-0.9%, Mg 0.6-0.9%, Si 0.6-0.9%, Fe impurity content is less than 0.2%, the content of each other impurity is less than 0.1%, and the balance is Al.

[0008] The present invention also provides a method for preparing the above-mentioned conductor material, comprising:

[0009] Step 1: Melting: Al-TiB2 precursor, pure aluminum, Al-Mg master alloy and Al-Si master alloy are used for batching, and the Al-TiB2 precursor is remelted and diluted to prepare TiB2 / Al-Mg-Si ceramic steel aluminum alloy ingot;

[0010] Step 2: homogenizing annealing the TiB2 / Al-Mg-Si ceramic steel aluminum alloy ingot;

[0011] Step 3: hot extrusion deforming the annealed TiB2 / Al-Mg-Si ceramic steel aluminum alloy ingot to obtain an extruded rod;

[0012] Step 4: Solution treatment of the extruded rod;

[0013] Step 5: Artificial aging of the aluminum rod after solution treatment;

[0014] Step 6: Drawing the artificially aged aluminum rod at room temperature;

[0015] Step 7: Perform low-temperature artificial aging or natural aging on the aluminum wire drawn at room temperature to obtain an ultra-high-strength TiB2 / Al-Mg-Si conductor material.

[0016] Preferably, in step 1, Al-TiB2 precursor, pure aluminum, Al-Mg master alloy and Al-Si master alloy are used for formulation, including: the mass fraction of TiB2 particles in the Al-TiB2 precursor is 5-7%, and the B / Ti stoichiometric ratio is 2.0-2.1; the mass fractions of the Al-Mg master alloy and the Al-Si master alloy added are 7-9% and 5-6%, respectively; the mass fraction of Mg element in the Al-Mg master alloy is 9-11%, and the mass fraction of Si element in the Al-Si master alloy is 11-13%.

[0017] Preferably, in step 1, the Al-TiB2 precursor is remelted and diluted to prepare a TiB2 / Al-Mg-Si porcelain steel aluminum alloy ingot:

[0018] a. Melt Al-TiB2 precursor and pure aluminum and heat them to 720-750°C, stir them to make them fully mixed and reacted, add Al-Mg master alloy and Al-Si master alloy to alloy them, and obtain a melt;

[0019] b. Use high-purity argon gas to refine the melt;

[0020] c. Pour the melt into a steel mold at a pouring temperature of 720-750°C to obtain a TiB2 / Al-Mg-Si ceramic steel aluminum alloy ingot.

[0021] Preferably, in step 2, the TiB2 / Al-Mg-Si ceramic aluminum alloy is subjected to homogenization annealing, including: keeping at 540-570°C for 12-24h, cooling to 250-300°C, and air cooling.

[0022] Preferably, in step 3, the ingot is preheated to 350-380° C. and then hot extrusion deformation is performed, the extrusion speed is 0.2-0.5 m / min, and the extrusion ratio is 1:18-25.

[0023] Preferably, in step 4, the extruded rod is subjected to a solution treatment at a solution temperature of 550 to 570° C. for a solution time of 30 to 60 min, and water quenching at room temperature.

[0024] Preferably, the artificial aging temperature in step 5 is 170-190° C., and the aging time is 1-8 hours.

[0025] Preferably, the aluminum rod after artificial aging is drawn at room temperature, the deformation is 60-99%, and the drawing speed is 10-20 m / min;

[0026] Preferably, the aluminum wire drawn at room temperature is subjected to low-temperature artificial aging, the aging temperature is 130-150° C., and the aging time is 1-8 hours.

[0027] The present invention provides an ultra-high strength TiB2 / Al-Mg-Si conductor material and a preparation method thereof, which has a simple process, is easy to promote, and can be mass-produced. TiB2 hard ceramic particles are added to Al-Mg-Si aluminum alloy to prepare a TiB2 / Al-Mg-Si composite material, thereby improving the elastic modulus of the material, thereby improving the structural rigidity of the conductor, and obtaining a more excellent sag characteristic. TiB2 particles can further improve the strength of Al-Mg-Si aluminum alloy from the perspective of reinforcing phase, and combined with appropriate composition control, the addition of TiB2 ceramic particles can hardly damage the conductivity of the conductor.

[0028] The ultra-high strength TiB2 / Al-Mg-Si conductor material (GB / T 23308-2009) prepared by the method of the present invention has more excellent physical and chemical properties, higher elastic modulus, strength and conductivity, wherein the elastic modulus is 73.0-73.3 GPa, the tensile strength is 404.2-409.4 MPa, and the conductivity is 56.3-56.5% IACS.

[0029] The ultra-high strength TiB2 / Al-Mg-Si conductor material provided by the present invention can be used in overhead transmission lines, conductor materials of high-strength and high-conductivity all-aluminum alloy stranded wires, and core materials of aluminum alloy core stranded wires. Specific application scenarios include newly built long-distance transmission energy-saving lines, transmission lines in special geographical conditions such as heavily polluted and coastal areas, ice-covered areas, ultra-high voltage AC / DC lines, and large-span transmission lines.

[0030] It is to be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present disclosure. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the invention and, together with the description, serve to explain the principles of the invention.

[0032] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0033] Figure 1 Schematic diagram of preparing TiB2 / Al-Mg-Si conductor material by different process paths according to an embodiment of the present invention;

[0034] Figure 2 The strength and conductivity of the TiB2 / Al-Mg-Si conductor material prepared by different process paths in the embodiments of the present invention;

[0035] Figure 3 The dislocation configuration, precipitate phase distribution and size statistics of the TiB2 / Al-Mg-Si conductor material prepared by different process paths in Example 1 of the present invention, wherein (a) is Comparative Example 1, (b) is Comparative Example 2, (c) is Comparative Example 3, (d) is Comparative Example 4, (e) is Example 1, and (f) is Example 2. DETAILED DESCRIPTION

[0036] Exemplary embodiments will be described in detail herein, examples of which are shown in the accompanying drawings. When the following description refers to the drawings, unless otherwise indicated, the same numbers in different drawings represent the same or similar elements. The embodiments described in the following exemplary embodiments do not represent all embodiments consistent with the present invention. Instead, they are merely examples of methods consistent with some aspects of the present invention as detailed in the appended claims.

[0037] It should be noted that:

[0038] Unless otherwise stated, the units used in this specification are all international standard units, and the numerical values ​​and numerical ranges appearing in the present invention should be understood to include the inevitable systematic errors in industrial production.

[0039] In this specification, the numerical range expressed using "a numerical value A to a numerical value B" means a range including the endpoints numerical values ​​A and B.

[0040] In the present specification, a numerical range expressed using "above" or "below" means a numerical range including the number.

[0041] In this specification, the word "may" means both performing a certain process and not performing a certain process.

[0042] In this specification, when "normal temperature" or "room temperature" is used, the temperature may be 15-25°C.

[0043] In this manual, the reagents or instruments used without indicating the manufacturer are all conventional products that can be obtained through commercial purchase.

[0044] In view of the current complex production process of Al-Mg-Si aluminum alloy wires and the market's increasingly higher requirements for their sag characteristics, strength and conductivity, this implementation scheme provides an ultra-high strength TiB2 / Al-Mg-Si conductor material. The composition of the TiB2 / Al-Mg-Si conductor material is 1.37% Ti, 0.63% B, 0.75% Mg, 0.75% Si, the Fe impurity content is less than 0.1%, the content of each other impurity is less than 0.1%, and the balance is aluminum.

[0045] This embodiment also provides a method for preparing the above-mentioned material, step 1: smelting: using Al-TiB2 precursor, pure aluminum, Al-Mg master alloy and Al-Si master alloy for batching, remelting and diluting the Al-TiB2 precursor to prepare TiB2 / Al-Mg-Si porcelain steel aluminum alloy ingot;

[0046] The solidification structure is improved by introducing TiB2 hard ceramic phase through smelting, which specifically includes the following steps: melting Al-TiB2 precursor and pure aluminum in a crucible melting furnace, heating to 720-750°C, stirring to fully mix and react, adding Al-Mg master alloy and Al-Si master alloy for alloying; b. refining the melt with high-purity argon gas; c. pouring into a steel mold at a pouring temperature of 720-750°C;

[0047] The mass fraction of TiB2 particles in the Al-TiB2 precursor is 5-7%, and the B / Ti stoichiometric ratio is 2.0-2.1.

[0048] The mass fraction of Mg element in the Al-Mg master alloy is 9-11%, preferably 10% (Al-10% Mg).

[0049] The mass fraction of Si element in the Al-Si master alloy is 11-13%, preferably 12% (Al-12%Mg).

[0050] The mass fractions of the Al-Mg master alloy and the Al-Si master alloy added are 7-9% and 5-6% respectively.

[0051] Step 2: homogenizing annealing the TiB2 / Al-Mg-Si ceramic steel aluminum alloy ingot; eliminating macro segregation through homogenizing annealing;

[0052] Specifically, homogenization annealing: homogenization annealing the ingot, keeping it at 540-570°C for 12-24h, cooling it to 250-300°C with the furnace, and air cooling; more preferably, homogenization annealing: homogenization annealing the ingot in a muffle furnace, keeping it at 560-570°C for 12-15h, cooling it to 270-300°C with the furnace, and air cooling;

[0053] Step 3: hot extrusion deforming the annealed TiB2 / Al-Mg-Si ceramic steel aluminum alloy ingot to obtain an extruded rod; the extrusion texture is regulated by using the ceramic phase through hot extrusion;

[0054] Specifically, hot extrusion deformation: the ingot is preheated to 350-380°C and then hot extruded to form an aluminum rod, the extrusion speed is 0.2-0.5 m / min, and the extrusion ratio is 1:18-25;

[0055] Step 4: Solution treatment of the extruded rod; high temperature and short time of solution treatment to prevent the deterioration of the structure by combining the ceramic phase;

[0056] Step 5: Artificially age the aluminum rod after the solid solution treatment; forming a dispersed precipitation phase through artificial aging;

[0057] Specifically, the extruded rod is subjected to a solution treatment, the solution temperature is 550-570°C, the solution time is 30-60 min, and the solution is quenched in water at room temperature; preferably, the solution temperature is 555-565°C, and the solution time is 30-45 min;

[0058] Artificial aging: artificial aging is performed on the solution treated aluminum rod, the aging temperature is 170-190°C, and the aging time is 1-8h; preferably, the artificial aging, the aging temperature is 170-180°C, and the aging time is 6-8h;

[0059] Step 6: Drawing the artificially aged aluminum rod at room temperature; drawing at room temperature significantly improves the strength by utilizing the interaction between the precipitated phase, the ceramic phase and the dislocation; drawing the artificially aged aluminum rod at room temperature, with a deformation of 60 to 99% and a drawing speed of 10 to 20 m / min; preferably, the deformation is 90 to 99% and the drawing speed is 15 to 20 m / min;

[0060] Step 7: Perform low-temperature artificial aging or natural aging on the aluminum wire drawn at room temperature to obtain ultra-high-strength TiB2 / Al-Mg-Si conductor material. Low-temperature artificial aging treatment utilizes high-density uniformly distributed dislocations to accelerate the desolvation of residual solid solution atoms and thus improve conductivity;

[0061] The low-temperature artificial aging has an aging temperature of 130-150°C and an aging time of 1-5 hours. Preferably, the aging temperature is 140-150°C and the aging time is 3-5 hours. The aging temperature and aging time of the low-temperature artificial aging need to be strictly controlled to prevent severe recovery of dislocations and severe coarsening of the precipitated phase.

[0062] The present invention is further explained below in conjunction with specific embodiments, but is not intended to limit the protection scope of the present invention.

[0063] Example 1

[0064] The preparation method of ultra-high strength TiB2 / Al-Mg-Si conductor material (optimized T9+3h) comprises the following steps:

[0065] Step 1 Ingredients: 1) Al-6%TiB2 precursor (aluminum-based base material containing 6% TiB2 particles by mass), the contents of Ti and B are 4.14% and 1.88% respectively, and the mass fraction of the precursor added is 33.3%;

[0066] 2) Al-10%Mg master alloy, the added mass fraction is 8.88%;

[0067] 3) Al-12%Si master alloy, with an addition mass fraction of 5.03%;

[0068] 4) Industrial pure aluminum (purity>99.7%), mass fraction is 52.79%;

[0069] 5) The composition of the TiB2 / Al-Mg-Si conductor material is 1.37% Ti, 0.63% B, 0.75% Mg, 0.75% Si, the Fe impurity content is less than 0.1%, and the content of each other impurity is less than 0.1%.

[0070] Melting: 1) Melt Al-6%TiB2 precursor and industrial pure aluminum in a crucible melting furnace, heat to 730°C, and stir to fully mix and react;

[0071] 2) adding Al-10%Mg and Al-12%Si master alloys for alloying;

[0072] 3) Refining the melt with high-purity argon for 5 minutes;

[0073] 4) Pour the melt into a steel mold at a pouring temperature of 720°C.

[0074] Step 2: Homogenization annealing: Use a muffle furnace to homogenize the ingot, keep it at 570℃ for 12h, cool it to 300℃ with the furnace, and air cool it;

[0075] Step 3: Hot extrusion deformation: The ingot is preheated to 380°C in a muffle furnace and then hot extruded. The extrusion speed is 0.2 m / min and the extrusion ratio is 1:20.

[0076] Step 4: Solution treatment: The extruded rod is solution treated in a muffle furnace at a solution temperature of 560°C for 30 minutes and quenched in water at room temperature;

[0077] Step 5: Artificial aging: The aluminum rod of step (5) is artificially aged in an aging furnace at a temperature of 170° C. for 7 h.

[0078] Step 6: Room temperature drawing: Use a drawing machine to draw the aluminum rod in step (6) at room temperature, with a deformation of 90% and a drawing speed of 10 m / min;

[0079] Step 7: Low-temperature artificial aging: The aluminum conductor material wire of step (7) is subjected to low-temperature artificial aging in an aging furnace, the aging temperature is 150° C., and the aging time is 3 h.

[0080] Example 2

[0081] This comparative example discloses a TiB2 / Al-Mg-Si conductor material (T9+8h), comprising the following steps:

[0082] Step 1: Ingredients: 1) Al-6%TiB2 precursor (aluminum-based parent material containing 6% TiB2 particles by mass), the contents of Ti and B are 4.14% and 1.88% respectively, and the mass fraction added to the precursor is 33.3%; 2) Al-10%Mg master alloy, the added mass fraction is 8.88%; 3) Al-12%Si master alloy, the added mass fraction is 5.03%; 4) industrial pure aluminum (purity>99.7%), the mass fraction is 52.79%; 5) The composition of TiB2 / Al-Mg-Si conductor material is 1.37%Ti, 0.63%B, 0.75%Mg, 0.75%Si, Fe impurity content is less than 0.1%, and the content of each other impurity is less than 0.1%.

[0083] Melting: 1) Melt Al-6%TiB2 precursor and industrial pure aluminum in a crucible melting furnace and heat to 730℃, stir to make them fully mixed and react; 2) Add Al-10%Mg and Al-12%Si intermediate alloys for alloying; 3) Use high-purity argon to refine the melt for 5 minutes; 4) Pour the melt into a steel mold at a pouring temperature of 720℃.

[0084] Step 2: Homogenization annealing: Use a muffle furnace to homogenize the ingot, keep it at 570℃ for 12h, cool it to 300℃ with the furnace, and air cool it;

[0085] Step 3: Hot extrusion deformation: The ingot is preheated to 380°C in a muffle furnace and then hot extruded. The extrusion speed is 0.2 m / min and the extrusion ratio is 1:20.

[0086] Step 4: Solution treatment: The extruded rod is solution treated in a muffle furnace at a solution temperature of 560°C for 30 minutes and quenched in water at room temperature;

[0087] Step 5: Artificial aging: The aluminum rod of step (5) is artificially aged in an aging furnace at a temperature of 170° C. for 7 h.

[0088] Step 6: Room temperature drawing: Use a drawing machine to draw the aluminum rod in step (6) at room temperature, with a deformation of 90% and a drawing speed of 10 m / min;

[0089] Step 7: Low-temperature artificial aging: The aluminum conductor material wire of step (7) is subjected to low-temperature artificial aging in an aging furnace, the aging temperature is 150° C., and the aging time is 8 h.

[0090] Comparative Example 1

[0091] This comparative example discloses a method for preparing a TiB2 / Al-Mg-Si conductor material (T6), comprising the following steps:

[0092] Step (1) ingredients: 1) Al-6%TiB2 precursor (aluminum-based matrix containing 6% TiB2 particles by mass), the contents of Ti and B are 4.14% and 1.88% respectively, and the mass fraction of the precursor added is 33.3%;

[0093] 2) Al-10%Mg master alloy, the added mass fraction is 8.88%;

[0094] 3) Al-12%Si master alloy, with an addition mass fraction of 5.03%;

[0095] 4) Industrial pure aluminum (purity>99.7%), mass fraction is 52.79%;

[0096] 5) The composition of the TiB2 / Al-Mg-Si conductor material is 1.37% Ti, 0.63% B, 0.75% Mg, 0.75% Si, the Fe impurity content is less than 0.1%, and the content of each other impurity is less than 0.1%.

[0097] Step (2) Melting: 1) Melting Al-6% TiB2 precursor and industrial pure aluminum in a crucible melting furnace, heating to 730° C., and stirring to allow them to fully mix and react;

[0098] 2) adding Al-10%Mg and Al-12%Si master alloys for alloying;

[0099] 3) Refining the melt with high-purity argon for 5 minutes;

[0100] 4) Pour the melt into a steel mold at a pouring temperature of 720°C.

[0101] Step (3) homogenization annealing: homogenization annealing is performed on the ingot in a muffle furnace at 570°C for 12 h, followed by furnace cooling to 300°C, and air cooling;

[0102] Step (4) hot extrusion deformation: the ingot is preheated to 380° C. in a muffle furnace and then hot extruded at an extrusion speed of 0.2 m / min and an extrusion ratio of 1:20;

[0103] Step (5) solution treatment: the extruded rod is solution treated in a muffle furnace at a solution temperature of 560° C. for 30 min and then quenched in water at room temperature;

[0104] Step (6) artificial aging: the aluminum rod of step (5) is artificially aged in an aging furnace at an aging temperature of 170° C. for 7 hours.

[0105] Comparative Example 2

[0106] This comparative example discloses a method for preparing a TiB2 / Al-Mg-Si conductor material (T3), comprising the following steps:

[0107] Steps (1) to (5) are exactly the same as those in Comparative Example 1;

[0108] Step (6) Room temperature drawing: The aluminum rod of step (5) is drawn at room temperature using a drawing machine, with a deformation amount of 90% and a drawing speed of 10 m / min;

[0109] Step (7) Natural aging: The aluminum wire of step (6) is placed at room temperature for natural aging for 7 days.

[0110] Comparative Example 3

[0111] This comparative example 3 discloses a method for preparing a TiB2 / Al-Mg-Si conductor material (T8), comprising the following steps:

[0112] Steps (1) to (6) are exactly the same as those in Comparative Example 2;

[0113] Step (7) artificial aging: the aluminum conductor material of step (6) is artificially aged in an aging furnace at an aging temperature of 170° C. for 4 hours.

[0114] Comparative Example 4

[0115] This comparative example discloses a method for preparing a TiB2 / Al-Mg-Si conductor material (T9), comprising the following steps:

[0116] Steps (1) to (5) are exactly the same as those in Control Example 1;

[0117] Step (6) artificial aging: the aluminum rod of step (5) is artificially aged in an aging furnace at a temperature of 170° C. for 7 hours;

[0118] Step (7) room temperature drawing: the aluminum rod of step (6) is drawn at room temperature using a drawing machine, with a deformation amount of 90% and a drawing speed of 10 m / min;

[0119] Step (8) Natural aging: The aluminum conductor material of step (7) is placed at room temperature for natural aging for 7 days.

[0120] Combined with Comparative Examples 1 to 4 and Examples 1 and 2, the simplified schematic diagram of the process flow, tensile strength and conductivity, and microstructure characterization are as follows: Figure 1 to Figure 3 As shown:

[0121] Figure 1 It is a schematic diagram of preparing TiB2 / Al-Mg-Si conductor materials by different process paths.

[0122] Figure 2 The strength and conductivity of TiB2 / Al-Mg-Si conductor materials prepared by different process paths. The T3 state of control example 2 and the T8 state of control example 3 are natural aging and artificial aging after room temperature deformation of supersaturated solid solution, respectively.

[0123] The tensile strength obtained in the T3 state is 354.5 MPa and the electrical conductivity is 43.9% IACS.

[0124] The tensile strength obtained in the T8 state is 335.0 MPa and the electrical conductivity is 50.3% IACS.

[0125] The strength of the material was greatly improved by performing room temperature deformation on the basis of the T6 state of control example 1. After room temperature deformation, only natural aging, i.e., T9 process, was performed, and the tensile strength was increased from 350.5MPa in the T6 state to 454.9MPa, an increase of 29.8%. The conductivity was increased from 46.1% IACS in the T6 state to 50.7% IACS.

[0126] After 3 hours of low-temperature artificial aging in Example 1, the tensile strength obtained decreased from 454.9 MPa in the T9 state to 427.4 MPa. The conductivity obtained was significantly improved from 50.7% IACS to 55.5% IACS.

[0127] After 8 h of low-temperature artificial aging in Example 2, the tensile strength obtained decreased from 427.4 MPa at 3 h to 406.8 MPa, while the electrical conductivity increased from 55.5% IACS at 3 h to 56.4% IACS.

[0128] Compared with the T8 process for preparing the traditional Al-Mg-Si aluminum alloy wire, the tensile strength of the TiB2 / Al-Mg-Si conductor material prepared by the process of Example 2 is greatly improved, and excellent conductivity is obtained.

[0129] Figure 3 The dislocation configuration, precipitate distribution and size statistics of TiB2 / Al-Mg-Si conductor materials prepared by different process paths are shown in Figure 1. Transmission electron microscopy analysis shows that the tilt axis is the

[001] crystal zone axis of the matrix. Figure 3 (a) is the bright field image of the T6 state of the control example 1 and the statistical results of the precipitate size. There are only sporadic dislocation lines in the matrix, and the dislocation density is low. <100> The needle-shaped precipitates are evenly dispersed in the matrix, and the size of the precipitates is about 3.3nm.

[0130] Figure 3 (b) and (c) correspond to the bright field images of the control example 2T3 and control example 3T8, respectively. The results show that after solution treatment and room temperature deformation, dislocations multiply under the interaction with the solid solution atoms, and dislocations are entangled to form dislocation walls and subgrains. After the supersaturated solid solution is deformed at room temperature, natural aging alone cannot fully precipitate the solid solution atoms, so no precipitation phase is observed in the matrix. When the supersaturated solid solution is artificially aged after deformation at room temperature, the solid solution atoms are fully precipitated under the promotion of dislocations, and at the same time, the dislocations undergo serious recovery, and the dislocation density is greatly reduced. Due to the accelerated promotion of dislocations during artificial aging precipitation, the precipitated phase formed is unevenly distributed, with a large size of about 5.3nm, and the size distribution of the precipitated phase is uneven.

[0131] Figure 3 (d) is the bright field image and precipitate size statistics of the T9 state of control example 4. After the T9 state is deformed at room temperature based on the T6 state, the dislocation density is greatly improved through the strong interaction between the precipitate phase and the dislocation, and the precipitate size does not change, which is about 3.0nm.

[0132] contrast Figure 3(c) and (d) show that compared with the room temperature deformation of the supersaturated solid solution by the T8 process, when the matrix of the dispersed precipitate phase is deformed at room temperature by the T9 process, the precipitates have a strong pinning effect on the dislocations, so that the dislocations cannot slip over a large range. Therefore, dislocations rarely get entangled to form dislocation walls, making the dislocation distribution more uniform and the dislocation density higher.

[0133] Figure 3 (e) and (f) are the bright field images and statistical results of the precipitate size of the T9 / 3h and T9 / 8h processes, respectively. After 3 hours of low-temperature artificial aging in Example 1, the distribution of dislocations, dislocation density and the size of the precipitates did not change significantly, and the uniform dislocation distribution, high dislocation density and dispersed fine precipitates were still maintained. The dislocations did not recover significantly, and the precipitates did not show serious coarsening, so their mechanical properties did not show a serious decrease compared to the T9 state. However, the electrical conductivity is significantly improved, which means that the solid solution atoms remaining in the matrix in the T6 state are fully desolvated during low-temperature artificial aging, reducing the scattering of free-moving electrons.

[0134] Example 2 After 8 hours of low-temperature artificial aging, the dislocations recovered significantly. However, compared with the T8 state, a higher density of dislocations remained in the matrix. The precipitated phase also coarsened to a certain extent, about 5.0 nm, and the precipitated phase changed from a dispersed distribution to an uneven distribution state.

[0135] Those skilled in the art will readily appreciate other embodiments of the present invention after considering the specification and practicing the invention disclosed herein. This application is intended to cover any variations, uses or adaptations of the present invention that follow the general principles of the present invention and include common knowledge or customary techniques in the art that are not disclosed by the present invention. The specification and examples are to be considered exemplary only, and the true scope and spirit of the present invention are indicated by the following claims.

[0136] It should be understood that the present invention is not limited to what has been described above and that various modifications and changes may be made without departing from its scope. The scope of the present invention is limited only by the appended claims.

Claims

1. An ultra-high strength TiB2 / Al-Mg-Si conductor material, characterized in that: According to the percentage by mass, it includes: Ti 1.1-1.6%, B 0.4-0.9%, Mg 0.6-0.9%, Si 0.6-0.9%, Fe impurity content is less than 0.2%, the content of each other impurity is less than 0.1%, and the balance is Al.

2. The method for preparing the ultra-high strength TiB2 / Al-Mg-Si conductor material according to claim 1, characterized in that: include: Step 1: Melting: Al-TiB2 precursor, pure aluminum, Al-Mg master alloy and Al-Si master alloy are used for batching, and the Al-TiB2 precursor is remelted and diluted to prepare TiB2 / Al-Mg-Si ceramic steel aluminum alloy ingot; Step 2: homogenizing annealing the TiB2 / Al-Mg-Si ceramic steel aluminum alloy ingot; Step 3: hot extrusion deforming the annealed TiB2 / Al-Mg-Si ceramic steel aluminum alloy ingot to obtain an extruded rod; Step 4: Solution treatment of the extruded rod; Step 5: Artificial aging of the aluminum rod after solution treatment; Step 6: Drawing the artificially aged aluminum rod at room temperature; Step 7: Perform low-temperature artificial aging or natural aging on the aluminum wire drawn at room temperature to obtain an ultra-high-strength TiB2 / Al-Mg-Si conductor material.

3. The method for preparing the ultra-high strength TiB2 / Al-Mg-Si conductor material according to claim 1, characterized in that: In step 1, Al-TiB2 precursor, pure aluminum, Al-Mg master alloy and Al-Si master alloy are used for preparation, including: the mass fraction of TiB2 particles in the Al-TiB2 precursor is 5-7%, and the B / Ti stoichiometric ratio is 2.0-2.1; the mass fractions of the Al-Mg master alloy and the Al-Si master alloy added are 7-9% and 5-6% respectively; the mass fraction of Mg element in the Al-Mg master alloy is 9-11%, and the mass fraction of Si element in the Al-Si master alloy is 11-13%.

4. The method for preparing the ultra-high strength TiB2 / Al-Mg-Si conductor material according to claim 1, characterized in that: In step 1, the Al-TiB2 precursor is remelted and diluted to prepare a TiB2 / Al-Mg-Si porcelain steel aluminum alloy ingot: a. Melt Al-TiB2 precursor and pure aluminum and heat them to 720-750°C, stir them to make them fully mixed and reacted, add Al-Mg master alloy and Al-Si master alloy to alloy them, and obtain a melt; b. Use high-purity argon gas to refine the melt; c. Pour the melt into a steel mold at a pouring temperature of 720-750°C to obtain a TiB2 / Al-Mg-Si ceramic steel aluminum alloy ingot.

5. The method for preparing the ultra-high strength TiB2 / Al-Mg-Si conductor material according to claim 1, characterized in that: In step 2, the TiB2 / Al-Mg-Si ceramic steel aluminum alloy is subjected to homogenization annealing, including: keeping at 540-570°C for 12-24h, cooling to 250-300°C, and air cooling.

6. The method for preparing the ultra-high strength TiB2 / Al-Mg-Si conductor material according to claim 1, characterized in that: In step 3, the ingot is preheated to 350-380° C. and then hot extruded at a speed of 0.2-0.5 m / min and an extrusion ratio of 1:18-25.

7. The method for preparing the ultra-high strength TiB2 / Al-Mg-Si conductor material according to claim 1, characterized in that: In step 4, the extruded rod is subjected to a solution treatment at a solution temperature of 550 to 570° C. for a solution time of 30 to 60 min, and water quenching at room temperature.

8. The method for preparing the ultra-high strength TiB2 / Al-Mg-Si conductor material according to claim 1, characterized in that: The artificial aging temperature in step 5 is 170-190° C., and the aging time is 1-8 hours.

9. The method for preparing the ultra-high strength TiB2 / Al-Mg-Si conductor material according to claim 1, characterized in that: The artificially aged aluminum rod is drawn at room temperature, the deformation is 60-99%, and the drawing speed is 10-20 m / min.

10. A method for preparing an ultra-high strength TiB2 / Al-Mg-Si conductor material, characterized in that: The aluminum wire drawn at room temperature is subjected to low-temperature artificial aging, the aging temperature is 130-150°C, and the aging time is 1-8h.

Citation Information

Patent Citations

  • Improved aluminum alloys and methods for producing the same

    CN104364409A

  • (TiB2 / Al-Cu) / Al-Cu-series aluminum-based composite material and preparation method thereof

    CN113322401A

  • Heat treatment process for improving age hardening capability of Al-Mg-Si-Zn series aluminum alloy or composite material thereof

    CN114277325A

  • High-conductivity aluminum material based on TiB2p / 6201 porcelain steel aluminum alloy as well as preparation method and application of high-conductivity aluminum material

    CN116590580A

  • High-elongation 6201 porcelain steel aluminum alloy based on TiB2 particle reinforcement as well as preparation method and application of high-elongation 6201 porcelain steel aluminum alloy

    CN116694962A